Speeding up Viedma Deracemization through Water-catalyzed and Reactant Self-catalyzed Racemization - Tortora, Carola; Mai, Christina; Cascella, Francesca; Mauksch, Michael; Seidel-Morgenstern, Andreas; Lorenz, Heike; Tsogoeva, Svetlana (ChemPhysChem, 2020)
Viedma deracemization is based on solution phase racemization, dissolution of racemic or scalemic conglomerates and crystal growth through autocatalytic cluster formation. With rate limiting racemization, its acceleration by appropriate catalysts may result in speeding up deracemization. A conglomerate-forming chiral compound may principally racemize directly, or via reverse of its formation reaction. For a hydrazine derivative, we investigated available racemization pathways in presence of pyrrolidine or thiourea amine as base catalysts: via Mannich or aza-Michael reaction steps and their reverse, or by enolization. Racemization by enolization was computationally found to dominate, both under water-free conditions and in presence of water, involving a multitude of different pathways. Faster racemization in presence of water resulted indeed in more rapid deracemization, when the base was pyrrolidine. Under water-free conditions, the role of water as enolization catalyst is assumed by chiral hydrazine itself – in autocatalytic racemization and in which both reactant and product are catalysts.
CRIS-Team Scopus Importer:2020-09-04
Keywords: autocatalysis; deracemization; enolization; racemization; stereochemistry